2020
DOI: 10.1001/jamaophthalmol.2020.2457
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Fluid Resolution and Visual Acuity Gain in Patients With Diabetic Macular Edema Using Deep Learning

Abstract: IMPORTANCE Large amounts of optical coherence tomographic (OCT) data of diabetic macular edema (DME) are acquired, but many morphologic features have yet to be identified and quantified.OBJECTIVE To examine the volumetric change of intraretinal fluid (IRF) and subretinal fluid (SRF) in DME during anti-vascular endothelial growth factor treatment using deep learning algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 46 publications
1
56
0
1
Order By: Relevance
“…Deep learning-based methods offer a new approach, enabling quick and accurate segmentation of pathological features 15,16 and providing more granular assessments of disease progression. 17,18 De Fauw et al 19 previously published a 2-stage deep learning system, involving segmentation as an intermediate representation, and assessed its accuracy when classifying macular diseases. Herein, we assessed the agreement of automated segmentations in deliberately challenging scans with AMD and DME against a reading center criterion standard that importantly involved manual human segmentation of entire OCT volumes, rather than selecting key sections as others have done.…”
mentioning
confidence: 99%
“…Deep learning-based methods offer a new approach, enabling quick and accurate segmentation of pathological features 15,16 and providing more granular assessments of disease progression. 17,18 De Fauw et al 19 previously published a 2-stage deep learning system, involving segmentation as an intermediate representation, and assessed its accuracy when classifying macular diseases. Herein, we assessed the agreement of automated segmentations in deliberately challenging scans with AMD and DME against a reading center criterion standard that importantly involved manual human segmentation of entire OCT volumes, rather than selecting key sections as others have done.…”
mentioning
confidence: 99%
“…A recent study monitored the HRF counts in diabetic retinopathy and diabetic macular edema in eyes that received anti-VEGF and steroid injections. This study reported a decrease in the number of HRF with either treatment, but a more marked decrease in the steroid group [42]. This biomarker provides an interesting avenue to monitor inflammatory activity in diabetic eye disease.…”
Section: Introductionmentioning
confidence: 59%
“…HRF count has been explored as a potential biomarker to assess inflammation in diabetic eye disease. Manual and automated approaches of the segmentation of these HRF have been tested [40][41][42]. A recent study monitored the HRF counts in diabetic retinopathy and diabetic macular edema in eyes that received anti-VEGF and steroid injections.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Schlegel is of particular importance given its recent deployment in a retrospective clinical analysis that was able to correlate fluid amounts to clinical outcomes. 28 A key difference in our study, however, is the additional segmentation of PED segmentation within the same network. This becomes feasible with this data set, because of the method of spatial injection that uses the layer segmentation software (Orion TM ).…”
Section: Discussionmentioning
confidence: 97%